2017
DOI: 10.18805/lr.v0i0.7290
|View full text |Cite
|
Sign up to set email alerts
|

The response of some physiological traits of chickpea (Cicer arietinum L.)to biochar and phosphorus fertilizer application

Abstract: This study assessed the response of photosynthesis, chlorophyll content (CC), stomatal conductance (SC) and intercepted radiation (IR) of chickpea to biochar (0, 5 10 and 20 t ha -1 ) and phosphorus (P) fertilizer (0 and 90 kg ha -1 ) rates in Thohoyandou, South Africa in 2013/2014 summer and winter seasons. Photosynthesis, CC, SC and IR were determined at vegetative and reproductive stages. Biochar increased SC and CC by 22 -49% and 57 -126%, respectively. P increased CC by up to 9% in the winter sowing. IR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Seed yield and harvest index Analysis demonstrated highly significant (P ≤ 0.01) differences amongst the tested genotypes, GE interaction and environments for seed yield (Table 1). Similar results were also documented by past researchers Macil et al (2017) for seed yield in chickpea genotypes. Across environments, the most productive genotype for seed yield was NKC-5-S-12 while the least productive was NDC-5-S-10 (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…Seed yield and harvest index Analysis demonstrated highly significant (P ≤ 0.01) differences amongst the tested genotypes, GE interaction and environments for seed yield (Table 1). Similar results were also documented by past researchers Macil et al (2017) for seed yield in chickpea genotypes. Across environments, the most productive genotype for seed yield was NKC-5-S-12 while the least productive was NDC-5-S-10 (Table 4).…”
Section: Resultssupporting
confidence: 91%
“…At higher fertilizer levels, phosphorus loss followed the same trend observed for the growth of crown diameter, suggesting a positive correlation between phosphorus loss and crown diameter growth. At the same time, phosphorus in the substrate material affects plant height [49]. Based on the one-yearlong observations, the biomass of A. fruticosa was stable.…”
Section: Comprehensive Appraisal Of Optimal Conditions Of Water and Fmentioning
confidence: 98%
“…The increased concentrations of NH 4 + -N and NO 3 --N in the soil positively correlated with the increasing NRA in the plant (Loussaert et al, 2018). NRA increases linearly with increasing nitrate fertilization (Loussaert et al, 2018). Purbajanti et al, (2019) showed that increasing N fertilization could significantly increase NRA of peanuts compared to without N fertilization.…”
Section: Estimated Response For Maize Variables Of Experimental Factorsmentioning
confidence: 92%
“…Biochar application of 20 tons ha -1 increased the concentration of NO 3 --N in soil solution (Major et al, 2012). The increased concentrations of NH 4 + -N and NO 3 --N in the soil positively correlated with the increasing NRA in the plant (Loussaert et al, 2018). NRA increases linearly with increasing nitrate fertilization (Loussaert et al, 2018).…”
Section: Estimated Response For Maize Variables Of Experimental Factorsmentioning
confidence: 93%